Thorium for Sustainable Nuclear Energy - Rafika HELAIMIA (My University, 2023)
Since the 1950s, there has been interest in using thorium in the nuclear fuel cycle as aprimary source of nuclear energy. This is due to its practicality and its likelihood of not becoming scarcein the future. However, in the 2000s, there was a revolution in the international arena to addressenvironmental, economic, and political issues such as global warming, greenhouse gas emissions,depletion of fossil fuels, nuclear proliferation dangers, lack of energy access, and insecurity. The goal ofimplementing a new nuclear strategy is to substitute thorium for uranium as a source of nuclear energy.This is because thorium is naturally abundant and helps to reduce the risk of nuclear accidents andradioactive contamination. Nevertheless, certain nations have faced obstacles in altering their nuclearapproach, mainly due to concerns about the risks associated with nuclear proliferation. But, there areongoing endeavors to realize a significant climate change stabilizing wedge through the implementationof thorium-based reactors. This article explains the properties of thorium, outlines the advantages of usingit, and highlights any limitations to its application, with the aim of addressing these concerns. (PDF) Thorium for Sustainable Nuclear Energy. Available from: https://www.researchgate.net/publication/374753205_Thorium_for_Sustainable_Nuclear_Energy [accessed Nov 06 2023].
This article explains the properties of thorium, outlines the advantages of usingit, and highlights any limitations to its application, with the aim of addressing these concerns. (PDF) Thorium for Sustainable Nuclear Energy. Available from: https://www.researchgate.net/publication/374753205_Thorium_for_Sustainable_Nuclear_Energy [accessed Nov 06 2023].